2024
DOI: 10.1172/jci.insight.170772
|View full text |Cite
|
Sign up to set email alerts
|

Linking adipose tissue eosinophils, IL-4, and leptin in human obesity and insulin resistance

James D. Hernandez,
Ting Li,
Hamza Ghannam
et al.

Abstract: BACKGROUND.Obesity is a multifactorial disease with adverse health implications including insulin resistance (IR). In patients with obesity, the presence of high circulating levels of leptin, deemed hyperleptinemia, is associated with IR. Recent data in mice with diet-induced obesity (DIO) show that a partial reduction in leptin levels improves IR. Additional animal studies demonstrate that IL-4 decreases leptin levels. In rodents, resident adipose tissue eosinophils (AT-EOS) are the main source of IL-4 and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…A recent human study highlights the significant reduction in adipose tissue eosinophil content among obese patients. 24 This finding underscores the obesity-resistant effect of eosinophils within this microenvironment. Notably, the protective effect of eosinophils against high-fat diet-induced obesity in mice was first reported in 2011 by Wu et al 9 Their study demonstrated that C57BL/6 mice lacking eosinophils (ΔdblGATA mice) and fed a high-fat diet exhibited increased body fat, impaired glucose tolerance, and decreased insulin sensitivity compared to their wild-type littermate control mice.…”
Section: Part 1: Impact Of Eosinophils On Adipocytesmentioning
confidence: 83%
See 2 more Smart Citations
“…A recent human study highlights the significant reduction in adipose tissue eosinophil content among obese patients. 24 This finding underscores the obesity-resistant effect of eosinophils within this microenvironment. Notably, the protective effect of eosinophils against high-fat diet-induced obesity in mice was first reported in 2011 by Wu et al 9 Their study demonstrated that C57BL/6 mice lacking eosinophils (ΔdblGATA mice) and fed a high-fat diet exhibited increased body fat, impaired glucose tolerance, and decreased insulin sensitivity compared to their wild-type littermate control mice.…”
Section: Part 1: Impact Of Eosinophils On Adipocytesmentioning
confidence: 83%
“…This omission is significant, considering recent human studies have shown that specifically adipose tissue eosinophils have more influence on weight gain and metabolic dysfunction in obesity. 24 , 77 Kuruvilla et al 78 observed a mild but significant decrease in BMI of severe asthma patients over 6 mo on anti–IL-5 therapy. Again, eosinophils were only measured in blood, not in body fat.…”
Section: Part 3: Host Metabolism–eosinophil Interactions In Obese Vs ...mentioning
confidence: 99%
See 1 more Smart Citation